The megalopa and juvenile development of Pachygrapsus transversus (Gibbes, 1850) (Decapoda, Brahyura) compared with other grapsid crabs - Flores, AAV; Negreiros-Fransozo, M. L.; Fransozo, A. (Brill Academic Publishers, 1998)
Megalopae were reared in the laboratory to the 7(th) crab stage. The megalopa and 1(st) crab stage are described and juvenile development was studied with emphasis on pleopodal differentiation. The megalopal phase, is easily identified, and shares with those of other Grapsinae and Plagusiinae big size, the presence of many natatory setae, and a series of conspicuous teeth on the inner margin of the dactyli from the 2(nd) to 4(th) walking leg. These features are regarded as adaptive for settlement in a wave-swept environment, such as the rocky marine intertidal where most of those species live. Fast development of juvenile pleopods is another characteristic of these subfamilies. In Pachygrapsus transversus, the sexes can be distinguished from the 2(nd) crab stage. Gonopod differentiation in males and the basic segmentation of all four pleopod pairs in females are already concluded at the 5(th) instar. A review of the available information indicated that settlement of large megalopae and fast juvenile development, preceding a precocious sexual maturity, are trends in Grapsinae and Plagusiinae. on the other hand, the Sesarminae pass through a more extensive juvenile instar sequence and presumably a delayed maturity.